Confirmation of quantitative trait loci for ethanol sensitivity in long-sleep and short-sleep mice. - Markel, P D; Bennett, B; Beeson, M; Gordon, L; Johnson, T E (Genome Research, 1997)
Initial insensitivity to alcohol is a strong predictor of human alcoholism, a widespread and heritable health problem. The Long Sleep and Short Sleep lines of mice were developed by genetic selection for high or low alcohol sensitivity. We have identified seven quantitative trait loci (QTLs) specifying differences in alcohol sensitivity using intercross progeny from these selected strains. These QTLs (Lorel-Lore7) together account for approximately 60% of the total genetic variance for this trait. This represents the first report of linkages for genes influencing alcohol action in any mammalian system using stringent, genome-wide mapping criteria.